Building pre-professional identity during translator education - experiences from the multilingual translation workshop at the university of Turku - Salo Pia; Veivo Outi; Salmi Leena (Aarhus University, 2025)
Against the backdrop of the constantly changing professional environment, translator education needs to invest in the work readiness and employability of its graduates. This article explores translation students’ emerging professional identity, referred to here as pre-professional identity (PPI) and its relevance for enhancing work readiness.. For this purpose, we have examined self-reflective essays written by translation students participating in a translation business simulation as part of their MA studies. The findings suggest that, in order to support students in building PPI, to facilitate the transition to the labour market, and to foster employability, it is useful to provide students with pedagogical approaches based on experiential learning combined with opportunities for critical self-reflection.